Production and Characterization of Enzyme β-Endoxylanase from Bacteria of Termite-intestinal System - A. A. Istri Ratnawati; Wuryanti Handayani; Ni Nyoman Tri Puspaningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
A mesophile bacteria isolated from intestinal systems of local-soil termite, produced an extracellular β-endoxylanase upon growth on xylan. Optimum production of the enzyme was found in media containing oatspelt xylan at 37oC after sixth hours. The activities of its β-endoxylanase on oat-spelt xylan was investigated. It had an optimum pH and temperature, 5.0 and 40o C, respectively. However, pH stability occurred between 5.08.0. The enzyme was stable at 40o C for four hours and possessed a half life of four hours. β-endoxylanase had an apparent molecular mass of 45.000 to 66.200 Dalton as determined by SDS-PAGE. Analysis of zymogram using SDS-Xylan-PAGE indicated that enzymes could degrade oat-spelt xylan as substrates.